Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Pertanian Provinsi Gorontalo - Yusliani Husain; Radia Hafid; Roy Hasiru; Irina Popoi (STIE Amkop Makassar, 2023)
This study aims to determine the influence of the work environment on employee performance at the Agriculture Agency of Gorontalo Province. This study used a quantitative approach with the Ex-post facto research method. The data used were primary data obtained from distributing questionnaires to the employees of the Agriculture Agency of Gorontalo Province. The samples included 42 respondents. Data analysis applied simple linear regression. The results show the influence of the work environment on the performance of Gorontalo Province employees. The influence of the work environment on employees performance is 76,6%, while the remaining 23,4% is explained by other variables not examined in this study.